Key concepts in educational assessment - Isaacs, Tina.; Sage eBooks (London : SAGE, 2013)
A quick reference guide to educational assessment, explains all key terms and provides further reading suggestions.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Educational evaluation; Electronic books